Studi Komparasi Refleksi Kontekstual QS. Yunus 40–41 dan Asy-Syura 15 Tentang Pluralisme Kontemporer Sosiologis-Integratif - Askweni; Komarudin Sassi (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the concept of pluralism in QS. Yunus: 40–41 and QS. Asy-Shura: 15 through a sociological-integrative approach. The study uses a library research method with an analytical-comparative design and a Muqāran approach to compare the interpretations of classical and contemporary commentators. Primary data are in the form of verses of the Qur'an and commentaries, while secondary data are obtained from journals, books, and literature related to pluralism and the sociological theory of religion. Data collection is carried out through documentation studies, then analyzed through the stages of verse identification, comparative interpretations, linguistic analysis, sociological interpretation using Durkheim and Berger's theories, and drawing conceptual synthesis. The results show that QS. Yunus: 40–41 emphasizes the recognition of religious plurality as sunnatullah, while QS. Asy-Shura: 15 emphasizes the principles of justice, dialogue, and non-coercion in religious life. This study also found a shift in interpretation from an exclusive-theological to an inclusive-contextual style. Thus, these two verses form a model of inclusive-dialogical pluralism that can become the theological foundation for religious moderation in the contemporary era.